MILK IN CHILDREN’S AND ADULTS’ DIET: BENEFICIAL EFFECTS AND POTENTIAL RISK - Ye.F. Lukushkina; O.K. Netrebenko; E.Yu. Baskakova (Вопросы современной педиатрии, 2011)
Cow’s milk is used for the nutrition of children and adults since ancient times; its favorable effects are described in medical and popular literature. During the last years, some unfavorable effects of extensive use of milk in nutrition of infants were revealed. First of all, cow’s milk is strong risk factor of iron-deficient anemia in infants. Besides, the study of big group of children who received big volumes of milk during first 6–24 months of life showed that that type of diet increase the risk of obesity and related pathological states in older age. Comparison of compound and effects of cow’s and breast milk is presented. Authors reviewed literature data on influence of cow’s milk on the risk of acne. The question of the use of cow’s milk in adults’ diet is still under discussion.Key words: children, milk, diet, safety, efficacy.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (4): 140–144)